Beyond gene duplication: A-to-I RNA editing–mediated stop codon readthrough modulates Dbf2 dosage to resolve pleiotropic conflicts - Yanfei Du; Yu Zhang; Chenhui Wang; Yi Huang; Mengchun Wu; Junqi Huang; Mengde Hou; Qinhu Wang; Cong Jiang; Huiquan Liu (Proceedings of the National Academy of Sciences, 2026)
Stop codon readthrough is widespread across eukaryotes and often dismissed as translational noise, yet its tissue/stage-specific occurrence suggests adaptive roles in proteome tuning. We asked whether readthrough-related mechanisms can mitigate stage-specific pleiotropic trade-offs without genomic change. In the filamentous ascomycete Fusarium graminearum , the functional solution relies on developmentally programmed A-to-I “stop-loss” RNA editing of the terminal NDR kinase gene FgDBF2 (UAG→UIG, read as UGG), instead of stochastic readthrough. This edit adds a short, intrinsically disordered C-terminal extension acting as a cis -encoded destabilizing element, lowering FgDbf2 dosage during ascospore formation. Genetic and cell biological analyses show meiosis proceeds independently of FgDbf2, but accurate one-nucleus/one-spore encapsulation is promoted by the edited, destabilized isoform. Blocking editing (stop retained) or increasing unedited FgDbf2 yields malformed, multinucleate spores despite normal nuclear counts, establishing ascospore morphogenesis as dosage-sensitive rather than isoform-specific. Conversely, constitutive production of the edited, destabilized isoform impairs vegetative growth and hyphal septation, suggesting stage-specific antagonism with mitotic functions. Mechanistically, the edited tail destabilizes Dbf2 and GFP, likely via nonclassical proteostasis pathways. Epistasis analysis indicates the CDK Cdc2A also restrains FgDbf2 and elevated Cdc2A partially suppresses defects caused by excess unedited FgDbf2. Comparative and transcriptomic analyses reveal conservation of DBF2 stop-loss editing across Sordariomycetes and identify many stop-loss edits encoding destabilizing tails consistent with positive genome-wide selection. We propose that stage-specific stop-loss editing is a developmentally gated dosage-buffering mechanism that transiently reduces NDR kinase abundance during ascospore formation, thereby alleviating growth–reproduction trade-offs without requiring gene duplication.